Republic of Korea : Staff Report for the 2013 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2013 Article IV Consultation highlights that the Republic of Korea has experienced impressive growth since the 1970s, enabling it to escape the middle-income trap. Policies should aim to tackle the weakness of domestic demand and counter forthcoming headwinds to potential growth. Korea is reaping the benefits of prudent macroeconomic management and financial moderation. The economy faces significant medium-term growth and inclusiveness challenges. Slow household income growth hinders stabilization in household debt and weighs on domestic demand, while services sector productivity is very low.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet